Electrode materials comprising layered sodium metal oxide, electrodes comprising the same and use of the same in electrochemistry

JP2025036725AInactive Publication Date: 2025-03-14HYDRO QUEBEC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2025001811
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2018-10-02
Filing Date
2025-01-06
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

Smart Images

  • Figure 2025036725000001_ABST
    Figure 2025036725000001_ABST
Patent Text Reader

Abstract

To provide electrode materials comprising an electrochemically active material, wherein the electrochemically active material comprises a P2-type or O3-type layered sodium metal oxide.SOLUTION: The present technology relates to electrode materials comprising an electrochemically active material, wherein the electrochemically active material comprises a P2-type or O3-type layered sodium metal oxide. The electrochemically active material has the formula NaxMO2 (where 0.5≤x≤1.0, and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb and combinations thereof. Electrodes, electrochemical cells and batteries comprising the electrode materials are also described. The technique relates to an electrochemical cell including an anode, a cathode and an electrolyte.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Related Applications This application claims priority under applicable law to U.S. Provisional Patent Application No. 62 / 740,185, filed October 2, 2018, the entire contents of which are incorporated herein by reference for all purposes.

[0002] Technical Field This application relates to the field of electrochemically active materials and their use in electrochemical applications. More particularly, this application relates generally to electrode materials comprising layered sodium metal oxides as electrochemically active materials, electrodes comprising them, methods for their manufacture and their use in electrochemical cells. [Background technology]

[0003] background Layered lithium metal oxides of formula LiMO2 (M = transition metal), such as oxides with layered structures like lithium cobalt oxide (LiCoO2) and lithium nickel oxide (LiNiO2), are cathode materials commercially used in lithium ion batteries (LIBs). Layered LiMO2 can be classified by their stacking geometry. Different types of stacking differ in the stacking sequence of the oxide layers, which changes the arrangement of the (MO2) sheets and the shape of the sites occupied by the lithium ions. The oxygen environment of the lithium ions can be, for example, octahedral (O), prismatic (P) or tetrahedral (T). Layered LiMO2 can also be characterized by the number of MO2 sheets found in a unit cell. The structure of layered LiMO2 has a significant effect on the electrochemical properties of the material, such as its capacity, cyclability and charge / discharge rates. Layered P2 and O3 type structures are of interest for use in electrochemical cells, for example.

[0004] One of the main drawbacks of currently used electrode materials, including layered oxides as electrochemically active materials, is their high production costs. For example, the rising price of lithium could be problematic for the increasing market share of LIBs. In fact, lithium is used in multiple components of conventional LIBs, such as the positive and negative electrodes as well as the electrolyte. Therefore, supply issues and the cost of lithium are at the heart of the main factors affecting their expansion into some commercial renewable energy applications.

[0005] Thus, there is a need for the development of new electrode materials, e.g., electrode materials that include P2 and / or O3 type layered oxides as electrochemically active materials, which eliminate one or more of the disadvantages of conventional layered oxide materials. Summary of the Invention [Means for solving the problem]

[0006] overview According to one aspect, the present technology provides an electrode material comprising an electrochemically active material, the electrochemically active material having the formula Na x The present invention relates to an electrode material comprising a layered sodium metal oxide of formula MO2, where 0.5≦x≦1.0 and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof.

[0007] In one embodiment, the electrochemically active material is - Formula Na x MO2 (wherein x is a number such that 0.5≦x≦0.8, and M is Co , Mn, Fe, Ni, Ti, Cr, V, Cu and combinations thereof), and - Formula Na x O3-type layered sodium metal oxide of MO2 (wherein x is a number such that 0.8≦x≦1.0 and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof) The layered sodium metal oxide is selected from the group consisting of:

[0008] In another embodiment, the electrochemically active material has the formula Na x M' 1-y M y O2 layered sodium metal oxide, where x and M are as defined herein, y is a number such that 0≦y≦1.0, and M′ is different from M and is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof.

[0009] In another embodiment, the electrochemically active material has the formula Na x M' 1-y Mn y O2 layered sodium metal oxide, where x is as defined herein, y is such that 0≦y≦1.0, and M′ is selected from Co, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof.

[0010] In another embodiment, the electrode material further comprises an electronically conductive material selected from carbon black, acetylene black, graphite, graphene, carbon fibers, carbon nanofibers, carbon nanotubes, and combinations thereof.

[0011] In another embodiment, the electrode material further comprises a binder selected from the group consisting of polyether type polymeric binders, fluorinated polymers, and water soluble binders.

[0012] According to another aspect, the present technology relates to an electrode comprising an electrode material as defined herein on a current collector. In one embodiment, the electrode is a positive electrode.

[0013] According to another aspect, the present technology relates to an electrochemical cell comprising an anode, a cathode and an electrolyte, the cathode being as defined herein. In one embodiment, the anode comprises metallic lithium. Alternatively, the anode comprises metallic sodium.

[0014] In another embodiment, the electrolyte is a liquid electrolyte comprising a salt in a solvent. Alternatively, the electrolyte is a gel electrolyte comprising a salt in a solvent and, optionally, a solvating polymer. According to another alternative, the electrolyte is a solid polymer electrolyte comprising a salt in a solvating polymer. In one embodiment, the salt is a lithium salt. Alternatively, the salt is a sodium salt.

[0015] According to another aspect, the present technology relates to a battery comprising at least one electrochemical cell as defined herein. In one embodiment, the battery is selected from a lithium ion battery and a sodium ion battery. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 is an X-ray diffraction pattern of P2-type layered sodium cobalt oxide powder of formula Na0.5CoO2 obtained using a solid-state method.

[0017] [Diagram 2] FIG. 2 is an X-ray diffraction pattern of the O3-type mixed layered sodium transition metal oxide powder of formula NaNi0.4Co0.2Mn0.4O2 obtained using a solid state method.

[0018] [Diagram 3] FIG. 3 displays the charge-discharge profile of cell 1, where charge-discharge was performed at 0.1 C and recorded vs. Li / Li+ at a temperature of 25° C.

[0019] [Figure 4] FIG. 4 displays the charge-discharge profiles of cell 1 at various cycle rates, where charge-discharge was performed at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C and 4 C and recorded vs. Li / Li+ at a temperature of 25° C.

[0020] [Diagram 5]Figure 5 shows a graph of capacity (mAh / g) as a function of cycle number, i.e., the aging curve of cell 1. Long cycle or cycle stability experiments were performed at a constant charge / discharge current of 1C and the results were recorded versus Li / Li+ at a temperature of 25°C.

[0021] [Figure 6] Figure 6 displays the charge-discharge profile of cell 2. Charge-discharge was performed at 0.3 C, at a temperature of 50 °C, and from 2.0 to 4.4 V vs. Li / Li+.

[0022] [Figure 7] Figure 7 shows the charge-discharge profile of cell 2. Charge-discharge was performed at 0.3 C, at a temperature of 80 °C, and from 2.0 to 4.4 V vs. Li / Li+.

[0023] [Figure 8] Figure 8 shows the charge-discharge profile of cell 3. Charges and discharges were performed at 0.1 C, at a temperature of 25 °C, and from 2.0 to 4.4 V vs. Li / Li+.

[0024] [Figure 9] FIG. 9 displays the charge-discharge profiles of cell 3 at various cycle rates, where charge-discharge was performed at 0.1 C, 0.2 C, 0.5 C, 1 C, 2 C and 4 C and recorded vs. Li / Li+ at a temperature of 25° C.

[0025] [Figure 10] Figure 10 shows a graph of capacity (mAh / g) as a function of cycle number for cell 3. Long cycle experiments were performed at a constant charge / discharge current of 2C and results were recorded vs. Li / Li+ at a temperature of 25°C.

[0026] [Figure 11] Figure 11 shows the initial charge-discharge curves of cell 4. Charge-discharge was performed at 0.1 C, at a temperature of 25°C, and from 2.0 to 4.4 V vs. Li / Li+.

[0027] [Figure 12]12 displays two charge / discharge profiles of cell 5, specifically the first and fifth cycles. Charge / discharge was performed at 0.3 C, at a temperature of 80° C., from 2.0 to 4.0 V vs. Li / Li+.

[0028] [Figure 13] FIG. 13 shows the charge / discharge profile of cell 6, which was charged / discharged at 0.1 C from 2.0 to 4.4 V vs. Li / Li+ at a temperature of 25° C.

[0029] [Figure 14] FIG. 14 shows the charge / discharge profile of cell 7, which was charged / discharged at 0.1 C from 2.0 to 4.4 V vs. Li / Li+ at a temperature of 25° C.

[0030] [Figure 15] FIG. 15 shows the charge / discharge profile of cell 8, which was charged / discharged at 0.1 C from 2.0 to 4.4 V vs. Li / Li+ at a temperature of 25° C.

[0031] [Figure 16] FIG. 16 shows the charge / discharge profile of cell 9, which was charged / discharged at 0.1 C from 2.0 to 4.5 V vs. Li / Li+ at a temperature of 25° C.

[0032] [Figure 17] FIG. 17 shows the charge / discharge profile of cell 10, which was charged / discharged at 0.1 C from 2.0 to 4.4 V vs. Li / Li+ at a temperature of 25° C.

[0033] [Figure 18] FIG. 18 shows the charge / discharge profile of cell 11, which was charged / discharged at 0.1 C from 2.0 to 4.4 V vs. Li / Li+ at a temperature of 25° C.

[0034] [Figure 19]Figure 19 shows a graph depicting the capacity (mAh / g) as a function of cycle number for cell 11. Long cycle experiments were performed at a constant charge / discharge current of 0.1 C and the results were recorded vs. Li / Li+ at a temperature of 25°C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] Detailed Description The following detailed description and examples are presented for purposes of illustration only and are not to be construed as further limiting the scope of the present invention.

[0036] All technical and scientific terms and expressions used herein have the same definitions as commonly understood by one of ordinary skill in the art. However, definitions of some of the terms and expressions used are provided below.

[0037] The term "approximately" or its equivalent, when used herein, means in the vicinity of or near. For example, when the term "approximately" or "about" is used in reference to a numerical value, it modifies it above and below a 10% variation from the nominal value. The term may also take into account, for example, experimental error or rounding of a measuring device.

[0038] When a range of values ​​is referred to in this application, the lower and upper limits of the range are always included in the definition, unless otherwise indicated.

[0039] The present technology relates to the use of layered oxides of sodium and at least one metallic element as electrochemically active materials, the layered oxides of sodium and at least one metallic element having a P2 or O3 type stacking.

[0040] In one example, the metallic element is a metal, such as a transition metal, a post-transition metal, a metalloid, an alkali metal, an alkaline earth metal, or a combination thereof, for example, the metal is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations of at least two thereof.

[0041] In one example, the electrochemically active material has the formula Na x The layered sodium metal oxides include those of formula MO2, where x is a number such that 0.5≦x≦1.0, and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof.

[0042] In another example, the electrochemically active material can be of the formula Na x The layered sodium metal oxides include a P2 type layered sodium metal oxide of the formula MO2, where x is a number such that 0.5≦x≦0.8, and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, and combinations thereof.

[0043] In another example, the electrochemically active material can be of the formula Na x The layered sodium metal oxides include O3-type layered sodium metal oxides of MO2, where x is a number such that 0.8≦x≦1.0, and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof.

[0044] In another example, the electrochemically active material can be of the formula Na x CoO2, where x is as defined herein. For example, the layered sodium cobalt oxide has a P2 type stack. An example of the layered sodium cobalt oxide is of the formula Na 0.5 Contains CoO2.

[0045] In another example, the electrochemically active material can be of the formula Na x MnO2 layered sodium manganese oxide, where x is as defined herein.

[0046] Further examples of electrochemically active materials include those of formula Na x M' 1-y M y and O2, wherein x and M are as defined herein, y is a number such that 0≦y≦1.0, and M′ is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof, and M is different from M′.

[0047] For example, the electrochemically active material may be of the formula Na x M' 1-y Mn y O2, where x and y are as defined herein, and M' is selected from Co, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof. For example, the electrochemically active material may be of the formula Na x (NiCo) 1-y Mn y O2, Na x Co 1-y Mn y O2, Na x Ni 1-y Mn y O2 and Na x (CoTi) 1-y Mn 1-y Non-limiting examples of electrochemically active materials include mixed layered oxides of Na, O, and ZnO, where x and y are as defined above. 0.5 CoO2, Na 0.67 CoO2, Na 0.67 Co 0.67 Mn 0.33 O2, Na 0.67 Ni 0.33 Mn 0.67 O2, Na 0.67 Co 0.6 Mn 0.4 O2, Na 0.67 Co 0.55 Mn 0.45 O2, Na 0.67 Co 0.5 Mn 0.5 O2, Na 0.67 Co 0.50 Mn 0.33 Ti 0.17 O2, Na 0.6 MnO2, NaNi 0.4 Co 0.2 Mn 0.4 O2 and NaNi 0.33 Fe 0.33 Mn 0.33 O2 is one example.

[0048] The electrochemically active material may be doped with other elements or impurities, present in small amounts as needed, for example to adjust or optimize its electrochemical properties. In some cases, the electrochemically active material may be doped by partial substitution of other ions of the metal (M). For example, the electrochemically active material may be doped with transition metals (e.g., Fe, Co, Ni, Mn, Ti, Cr, Cu, V) and / or metals other than transition metals (e.g., Mg, Al, Sb).

[0049] The electrochemically active material described herein is preferably substantially free of lithium. For example, the electrochemically active material contains less than 2 wt%, less than 1 wt%, less than 0.5 wt%, less than 0.1 wt%, less than 0.05 wt%, or less than 0.01 wt% lithium. Thus, the electrochemically active material can potentially reduce production costs compared to the corresponding P2-type or O3-type lithium metal oxide structure. The electrochemically active material can also retain the same structure as the corresponding P2-type or O3-type lithium metal oxide structure and have similar electrochemical performance.

[0050] The present technology also relates to electrode materials comprising the electrochemically active materials described herein. In one example, the electrode materials described herein may further comprise an electronically conductive material. Non-limiting examples of electronically conductive materials include carbon black, Ketjen TM Carbon, Super P TM Carbon, Acetylene Black, Shawinigan Carbon, Denka TM Examples of the electronically conductive material include carbon black, graphite, graphene, carbon fibers (e.g., vapor grown carbon fibers (VGCF)), carbon nanofibers, carbon nanotubes, or a combination of at least two of these. According to one example, the electronically conductive material is Ketjen TM According to one alternative, the electronic conducting material is Super P TM According to another alternative, the electronically conductive material is VGCF.

[0051] The electrode materials described herein may also further include a binder. For example, the binder is selected for its compatibility with the various elements of the electrochemical cell. Any known compatible binder is contemplated. For example, the binder is selected from polyether type polymer binders, fluorinated polymers, and water-soluble binders (water-soluble). According to one example, the binder is a fluorinated polymer such as polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE). According to another example, the binder may be a fluorinated polymer such as polyvinylidene fluoride (PVdF) or polytetrafluoroethylene (PTFE). is a water-soluble binder such as styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), hydrogenated NBR (HNBR), epichlorohydrin rubber (CHR) or acrylate rubber (ACM), and optionally comprises a thickener such as carboxymethylcellulose (CMC) or a polymer such as poly(acrylic acid) (PAA), poly(methacrylic acid) (PMMA) or a combination thereof. According to one example, the binder is a polymeric binder of polyether type. For example, the polymeric binder of polyether type is linear, branched and / or crosslinked and is based on poly(ethylene oxide) (PEO), poly(propylene oxide) (PPO) or a combination of the two (such as EO / PO copolymers), and optionally comprises crosslinkable units. In one variant of interest, the binder is PVdF or a polymer of polyether type as defined herein.

[0052] The electrode materials described herein may further optionally include additional components or additives, such as inorganic particles, glass or ceramic particles, ionic conductors, salts (e.g., lithium salts), and other similar additives.

[0053] The present technology also relates to an electrode comprising the electrode material defined herein on a current collector (e.g., aluminum, copper). Alternatively, the electrode may be free-standing. In one variant of interest, the electrode is a positive electrode.

[0054] The present technology also relates to an electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode is as defined herein.

[0055] In one example, the electrochemically active material of the negative electrode or counter electrode may be selected from any known compatible material. For example, the electrochemically active material of the negative electrode may be selected for its electrochemical compatibility with the electrochemically active material defined herein. For example, the electrochemically active material of the negative electrode may include an alkali metal film, such as a metallic lithium film, a metallic sodium film, or a film of an alloy containing at least one of them.

[0056] The electrolyte is also selected for its compatibility with the various components of the electrochemical cell. Any type of compatible electrolyte is contemplated. According to one example, the electrolyte is a liquid electrolyte comprising a salt in a solvent. According to one alternative, the electrolyte is a gel electrolyte comprising a salt in a solvent and, optionally, a solvating polymer. According to another alternative, the electrolyte is a solid polymer electrolyte comprising a salt in a solvating polymer.

[0057] The salt is preferably an ionic salt, such as a lithium salt or a sodium salt. Non-limiting examples of lithium salts include lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazolate (LiTDI), lithium 4,5-dicyano-1,2,3-triazolate (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiTf), and lithium fluoroalkylphosphate. Li[PF3(CF2CF3)3] (LiFAP), lithium tetrakis(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolate(2-)-O,O')borate [B(CO)2] (LiBBB) and combinations thereof. According to a variant of the first object, the lithium salt is LiP F6. According to a variant of the second object, the lithium salt is LiFSI. According to a variant of the third object, the lithium salt is LiTFSI. Non-limiting examples of sodium salts include the above salts, in which the lithium ion is replaced by a sodium ion.

[0058] The solvent, when present in the electrolyte, may be a polar aprotic non-aqueous solvent. Non-limiting examples of the solvent include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) and vinylene carbonate (VC), acyclic carbonates such as dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) and dipropyl carbonate (DPC), lactones such as γ-butyrolactone (γ-BL) and γ-valerolactone (γ-VL), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, etc. These include acyclic ethers such as diphenyl ether (DEE), ethoxymethoxyethane (EME), trimethoxymethane and ethyl monoglyme, cyclic ethers such as tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane and dioxolane derivatives, and other solvents such as dimethyl sulfoxide, formamide, acetamide, dimethylformamide, acetonitrile, propylnitrile, nitromethane, phosphoric acid triesters, sulfolane, methylsulfolane, propylene carbonate derivatives and mixtures thereof.

[0059] Examples of electrolytes include lithium hexafluorophosphate (LiPF6) dissolved in a non-aqueous solvent mixture such as a mixture of ethylene carbonate and diethyl carbonate (EC / DEC) ([3:7] by volume) or a mixture of ethylene carbonate and dimethyl carbonate (EC / DMC) ([4:6] by volume).

[0060] When the electrolyte is a gel electrolyte or a polymer gel electrolyte, the gel polymer electrolyte may include, for example, a polymer precursor and a salt (e.g., a salt as defined above), a solvent, and, if necessary, a polymerization and / or crosslinking initiator. Non-limiting examples of gel electrolytes include, but are not limited to, those described in WO2009 / 111860 (Zaghib et al.) and WO The method is described in PCT patent application published under number 2004 / 068610 (Zaghib et al.). Examples of the gel electrolyte include a gel electrolyte.

[0061] The electrolyte may also be a solid polymer electrolyte (SPE) comprising a salt in a solvating polymer. Any type of known compatible SPE is contemplated. For example, the SPE is selected for its compatibility with various components of an electrochemical cell. For example, the SPE is selected for its compatibility with lithium and / or sodium. The SPE may generally comprise a salt and one or more solid polar polymers, optionally crosslinked. Polyether-type polymers, such as those based on poly(ethylene oxide) (PEO), may also be used, although several other compatible polymers for SPE preparation are known and are contemplated as well. By way of example, the polymer may be further crosslinked. Examples of such polymers include branched polymers, such as those disclosed in WO 2003 / 063287 (Zaghib et al.) Examples of such polymers include star or comb polymers such as those described in the PCT patent applications filed on 2006 / 023363.

[0062] The gel electrolyte or liquid electrolyte defined above may also be impregnated with a separator, such as a polymer separator. Non-limiting examples of separators include polyethylene (PE), polypropylene (PP), cellulose, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF) and polypropylene-polyethylene-polypropylene (PP / PE / PP) membranes. For example, the separator may be a Celgard PE membrane. TM This type of commercially available polymer separator.

[0063] The electrolyte may also optionally contain additional components or additives such as ion conductors, inorganic particles, glass or ceramic particles, e.g., nanoceramics (such as Al2O3, TiO2, SiO2 and other similar compounds), and other similar additives.

[0064] The present technology also generally relates to a battery comprising at least one electrochemical cell as defined herein. For example, the battery is selected from a lithium battery, a lithium ion battery, a sodium battery and a sodium ion battery. According to one variant of the object, the battery is a lithium battery or a lithium ion battery. EXAMPLES

[0065] The following examples are for illustrative purposes and should not be construed as further limiting the scope of the contemplated invention, which are better understood with reference to the accompanying drawings.

[0066] Example 1 Synthesis of electrochemically active materials

[0067] Using solid-state reaction techniques, the formula Na 0.5 CoO2, Na 0.67 CoO2, Na 0.67 Co 0.67 Mn 0.33 O2, Na 0.67 Ni 0.33 Mn 0.67 O2, Na 0.67 Co 0.6 Mn 0.4 O2, Na 0.67 Co 0.55 Mn 0.45 O2, Na 0.67 Co 0.5 Mn 0.5 O2, Na 0.67 Co 0.50 Mn 0.33 Ti 0.17 O2, Na 0.6 MnO2, NaNi 0.4 Co 0.2 Mn 0.4 O2 and NaNi 0.33 Fe 0.33 Mn 0.33Layered oxides of O2 were prepared. Each precursor (Na2CO3 and metal oxides such as Mn2O3, Co2O3, NiO, Fe2O3 and TiO2) was weighed to obtain the desired stoichiometry. Samples were prepared by crushing and mixing the precursor powders. The crushed and mixed precursor powders were then placed in an oven and heated between 700 °C and 1000 °C under air or oxygen atmosphere for 5 to 24 hours.

[0068] Example 2 Characterization of electrochemically active materials a) Powder X-ray diffraction (XRD)

[0069] The atomic and molecular structures of the electrochemically active materials were examined by X-ray diffraction performed on both the P2-type and O3-type layered sodium metal oxide structures prepared in Example 1. 0.5 Figure 2 shows the X-ray diffraction pattern of CoO2 powder. 0.4 Co 0.2 Mn 0.4 The X-ray diffraction pattern of O2 powder is shown.

[0070] Example 3 Electrochemical properties

[0071] All cells were assembled in 2032-type coin cell housings with the components indicated in Table 1 and a negative electrode comprised of a metallic lithium film on an aluminum current collector. Cells containing liquid electrolyte were Celgard 1000V impregnated with a 1 M solution of LiPF6 in an EC / DEC mixture ([3:7] by volume) or an EC / DMC mixture ([4:6] by volume). TM The cells containing the solid polymer electrolyte were assembled using SPEs containing LIFSI or LITFSI. Table 1. Cell composition [Table 1]

[0072] a) P2 type Na 0.67 Electrochemical behavior of CoO2 This example illustrates the P2-type layered Na 0.67 Illustrates the electrochemical behavior of CoO2 materials.

[0073] Figure 3 shows the charge / discharge profile of cell 1. Charge / discharge was performed at 0.1 C and Li / Li at 25 °C. + Cell 1 delivered a capacity of approximately 104 mAh / g.

[0074] Figure 4 shows the charge-discharge profiles of cell 1 at various cycle rates. Charges and discharges were performed at 0.1C, 0.2C, 0.5C, 1C, 2C and 4C with Li / Li at 25°C. + At a cycle rate of 4C, Cell 1 delivered a capacity of approximately 92 mAh / g, effectively demonstrating 87% capacity retention with increasing cycle rates from 0.5C to 4C.

[0075] FIG. 5 shows a graph of the capacity (mAh / g) as a function of cycle number for cell 1. Long cycle experiments were performed at a constant charge / discharge current of 1C. The results are shown in Table 1 for Li / Li at a temperature of 25° C. + Figure 5 shows approximately 97% capacity retention after 200 cycles.

[0076] The effect of binder choice and cycle temperature is demonstrated in FIGS.

[0077] Figure 6 shows the charge / discharge profile of cell 2. The charge / discharge rate is 0.3 C, the temperature is 50 °C, and the Li / Li + The tests were performed between 2.0 and 4.4 V vs. Cell 2. Cell 2 delivered a capacity of approximately 107 mAh / g.

[0078] Figure 7 shows the charge / discharge profile of cell 2. The charge / discharge rate is 0.3 C, the temperature is 80 °C, and the Li / Li + The tests were performed between 2.0 and 4.4 V vs. Cell 2. Cell 2 delivered a capacity of approximately 107 mAh / g.

[0079] b) P2 type Na 0.67Co 0.67 Mn 0.33 Electrochemical behavior of O2 This example illustrates the P2-type layered Na 0.67 Co 0.67 Mn 0.33 Illustrates the electrochemical behavior of O2 materials.

[0080] Figure 8 shows the charge / discharge profile of cell 3. The charge / discharge rates are 0.1C and Li / Li at 25°C. + The tests were performed between 2.0 and 4.4 V vs. Cell 3. Cell 3 delivered a capacity of approximately 150 mAh / g.

[0081] FIG. 9 displays the charge-discharge profiles of cell 3 at various cycle rates. Charges and discharges were performed at 0.1C, 0.2C, 0.5C, 1C, 2C and 4C with Li / Li at 25° C. + At a cycle rate of 4C, Cell 3 delivered a capacity of approximately 121 mAh / g, effectively demonstrating 80% capacity retention with increasing cycle rates from 0.1C to 4C.

[0082] FIG. 10 shows a graph of capacity (mAh / g) as a function of cycle number for cell 3. Long cycle experiments were performed at a constant charge / discharge current of 2C. The results are for Li / Li + Figure 10 shows approximately 93.4% capacity retention after 100 cycles.

[0083] c) P2 type Na 0.67 Ni 0.33 Mn 0.67 Electrochemical behavior of O2 This example illustrates the P2-type layered Na 0.67 Ni 0.33 Mn 0.67 Illustrates the electrochemical behavior of O2 materials.

[0084] FIG. 11 shows the initial charge / discharge curves of cell 4. The charge / discharge curves are 0.1 C, Li / Li at 25° C. +The tests were performed between 2.0 and 4.4 V vs. Cell 4. Cell 4 delivered a capacity of approximately 182 mAh / g.

[0085] FIG. 12 displays two charge-discharge profiles of cell 5, namely the first and fifth cycles. Charge-discharge is performed at 0.3 C, at a temperature of 80° C., with Li / Li + The test was performed between 2.0 and 4.0 V vs. Cell 5. Cell 5 delivered a capacity of approximately 120 mAh / g.

[0086] d) P2 type Na 0.67 Co 0.6 Mn 0.4 Electrochemical behavior of O2 This example illustrates the P2-type layered Na 0.67 Co 0.6 Mn 0.4 Illustrates the electrochemical behavior of O2 materials.

[0087] FIG. 13 shows the charge / discharge profile of cell 6. The charge / discharge was performed at 0.1 C, Li / Li at 25° C. + The tests were performed between 2.0 and 4.4 V vs. Cell 6. Cell 6 delivered a capacity of approximately 142 mAh / g.

[0088] e) P2 type Na 0.67 Co 0.55 Mn 0.45 Electrochemical behavior of O2 This example illustrates the P2-type layered Na 0.67 Co 0.55 Mn 0.45 Illustrates the electrochemical behavior of O2 materials.

[0089] FIG. 14 shows the charge / discharge profile of cell 7. The charge / discharge was performed at 0.1 C, Li / Li at 25° C. + The test was performed between 2.0 and 4.4 V for cell 7. The cell This resulted in a capacity of h / g.

[0090] f) P2 type Na 0.67 Co 0.5 Mn 0.5Electrochemical behavior of O2 This example illustrates the P2-type layered Na 0.67 Co 0.5 Mn 0.5 Illustrates the electrochemical behavior of O2 materials.

[0091] FIG. 15 shows the charge / discharge profile of cell 8. The charge / discharge was performed at 0.1 C, Li / Li at 25° C. + The test was performed between 2.0 and 4.4 V vs. Cell 8. Cell 8 delivered a capacity of approximately 114 mAh / g.

[0092] g) P2 type Na 0.67 Co 0.50 Mn 0.33 Ti 0.17 Electrochemical behavior of O2 This example illustrates the P2-type layered Na 0.67 Co 0.50 Mn 0.33 Ti 0.17 Illustrates the electrochemical behavior of O2 materials.

[0093] FIG. 16 shows the charge / discharge profile of cell 9. The charge / discharge was performed at 0.1 C, Li / Li at 25° C. + The tests were performed between 2.0 and 4.5 V vs. Cell 9. Cell 9 delivered a capacity of approximately 137 mAh / g.

[0094] h) P2 type Na 0.60 Electrochemical behavior of MnO2 This example illustrates the P2-type layered Na 0.60 Illustrates the electrochemical behavior of MnO2 materials.

[0095] FIG. 17 shows the charge / discharge profile of cell 10. The charge / discharge rates are 0.1 C, Li / Li at 25° C. + The test was performed between 2.0 and 4.4 V vs. Cell 10. Cell 10 delivered a capacity of approximately 73 mAh / g.

[0096] i) O3 type NaNi 0.4 Co 0.2 Mn 0.4Electrochemical behavior of O2 This example illustrates the O3-type layered NaNi 0.4 Co 0.2 Mn 0.4 Illustrates the electrochemical behavior of O2 materials.

[0097] FIG. 18 shows the charge / discharge profile of cell 11. The charge / discharge was performed at 0.1 C, Li / Li at 25° C. + The test was performed between 2.0 and 4.4 V vs. Cell 11. Cell 11 delivered a capacity of approximately 118 mAh / g.

[0098] FIG. 19 shows a graph of capacity (mAh / g) as a function of cycle number for cell 11. Long cycle experiments were performed at a constant charge / discharge current of 0.1 C. The results are for Li / Li + Figure 19 shows good capacity retention after 50 cycles.

[0099] Numerous modifications can be made to any of the above embodiments without departing from the contemplated scope of the invention. All references, patents or scientific literature documents referred to in this application are incorporated herein by reference in their entirety for all purposes.

[0100] According to a preferred embodiment of the present invention, for example, the following is provided: (Section 1) An electrode material comprising an electrochemically active material, the electrochemically active material having the formula Na x MO 2 wherein x is a number such that 0.5≦x≦1.0, and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof. (Section 2) The electrochemically active material is - Formula Na x MO 2 wherein x is a number such that 0.5≦x≦0.8, and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, and combinations thereof; and - Formula Na x MO 2 wherein x is a number such that 0.8≦x≦1.0 and M is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof; Item 2. The electrode material according to item 1, comprising a layered sodium metal oxide selected from the group consisting of: (Section 3) The electrochemically active material has the formula Na x M’1-y M y O 2 wherein x and M are as described in item 1 or 2 above, y is a number such that 0≦y≦1.0, and M′ is different from M and is selected from Co, Mn, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof. (Section 4) The electrochemically active material has the formula Na x M’ 1-y Mn y O 2 wherein x is as defined in item 1 or 2 above, y is a number such that 0≦y≦1.0, and M′ is selected from Co, Fe, Ni, Ti, Cr, V, Cu, Sb, and combinations thereof. (Section 5) The electrochemically active material has the formula Na x Chief of Staff 2 5. The electrode material according to any one of items 1 to 4, comprising a layered sodium cobalt oxide of the formula: (Section 6) The electrochemically active material has the formula Na x MnO 2 5. The electrode material according to any one of items 1 to 4, comprising a layered sodium manganese oxide represented by the formula: (Section 7) The electrochemically active material has the formula Na x (NiCo) 1-y Mn y O 2 5. The electrode material according to any one of items 1 to 4, comprising a layered sodium metal oxide represented by the formula: (Section 8) The electrochemically active material has the formula Na x Co 1-y Mn y O 2 5. The electrode material according to any one of items 1 to 4, comprising a layered sodium metal oxide represented by the formula: (Section 9) The electrochemically active material has the formula Na x Ni 1-y Mn y O 2 5. The electrode material according to any one of items 1 to 4, comprising a layered sodium metal oxide represented by the formula: (Section 10) The electrochemically active material has the formula Na x (CoTi) 1-y Mn 1-y O 2 5. The electrode material according to any one of items 1 to 4, comprising a layered sodium metal oxide represented by the formula: (Section 11) 11. The electrode material according to any one of items 1 to 10, further comprising an electron conductive material. (Section 12) Item 12. The electrode material according to item 11, wherein the electronic conductive material is selected from carbon black, acetylene black, graphite, graphene, carbon fiber, carbon nanofiber, carbon nanotube, and combinations thereof. (Section 13) Item 13. The electrode material according to item 12, wherein the electronic conductive material comprises carbon fiber. (Section 14) Item 14. The electrode material according to item 13, wherein the carbon fiber is a vapor grown carbon fiber (VGCF). (Section 15) Item 13. The electrode material according to item 12, wherein the electronic conductive material comprises carbon black. (Section 16) The carbon black is Super P TM Item 16. The electrode material according to item 15, which is carbon. (Section 17) The carbon black is TM Item 16. The electrode material according to item 15, which is carbon. (Section 18) 18. The electrode material according to any one of items 1 to 17, further comprising a binder. (Section 19) Item 19. The electrode material according to item 18, wherein the binder is selected from the group consisting of polyether-type polymer binders, fluorinated polymers and water-soluble binders. (Section 20) 20. The electrode material according to item 19, wherein the binder is a fluorinated polymer. (Section 21) 21. The electrode material according to item 20, wherein the fluorinated polymer is polyvinylidene fluoride (PVdF). (Section 22) 21. The electrode material according to item 20, wherein the fluorinated polymer is polytetrafluoroethylene (PTFE). (Section 23) 20. The electrode material according to item 19, wherein the binder is a polyether type polymer binder. (Section 24) 24. The electrode material according to item 23, wherein the polyether type polymer binder is branched and / or crosslinked. (Section 25) 25. The electrode material according to claim 23 or 24, wherein the polyether type polymer binder is based on polyethylene oxide (PEO). (Section 26) 26. An electrode comprising the electrode material according to any one of items 1 to 25 on a current collector. (Section 27) 27. The electrode according to claim 26, wherein the electrode is a positive electrode. (Section 28) 28. An electrochemical cell comprising a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode is as described in item 26 or 27. (Section 29) 29. The electrochemical cell of claim 28, wherein the negative electrode comprises metallic lithium. (Section 30) 29. The electrochemical cell of claim 28, wherein the negative electrode comprises metallic sodium. (Section 31) 31. The electrochemical cell according to any one of items 28 to 30, wherein the electrolyte is a liquid electrolyte containing a salt in a solvent. (Section 32) 31. The electrochemical cell according to any one of items 28 to 30, wherein the electrolyte is a gel electrolyte containing a salt in a solvent and, if necessary, a solvated polymer. (Section 33) 31. The electrochemical cell according to any one of items 28 to 30, wherein the electrolyte is a solid polymer electrolyte containing a salt in a solvated polymer. (Section 34) 34. The electrochemical cell according to any one of items 31 to 33, wherein the salt is a lithium salt. (Section 35) 34. The electrochemical cell according to any one of items 31 to 33, wherein the salt is a sodium salt. (Section 36) 36. A battery comprising at least one electrochemical cell according to any one of items 28 to 35. (Section 37) 37. The battery according to claim 36, wherein the battery is selected from a lithium ion battery and a sodium ion battery. (Section 38) Item 38. The battery according to item 36 or 37, wherein the battery is a lithium ion battery. (Section 39) Item 38. The battery according to item 36 or 37, wherein the battery is a sodium ion battery.

Claims

[Claim 1] The invention described in the specification.